The use of small games in developing motor and skill competencies among primary school students: "A field study of some primary schools in Central Algiers." - safia, Touchen (Journal of Sport Science Technology and Physical Activities, 2026)
This study aims to highlight the role of small games in developing motor and skill competencies among primary school students. For this purpose, a descriptive method was adopted, and the sample consisted of 12 teachers from the central Algiers region. The sample was intentional, and the triadic method was used to find the significant percentages of the data. Additionally, the Chi-square test was used to clarify the statistically significant differences at the alpha significance level of 0.05. The study revealed that small games are frequently used in physical education classes for students. The results confirmed that these games contribute to the development of motor skills and enhance their interaction during the class. Therefore, small games are considered an effective means to improve their motor performance. Based on this, the study recommended increasing the use of small games in physical education and sports classes to enhance motor skills and stimulate greater interaction among students.